2011
DOI: 10.1073/pnas.1112605108
|View full text |Cite
|
Sign up to set email alerts
|

Visuoauditory mappings between high luminance and high pitch are shared by chimpanzees (Pan troglodytes) and humans

Abstract: Humans share implicit preferences for certain cross-sensory combinations; for example, they consistently associate higher-pitched sounds with lighter colors, smaller size, and spikier shapes. In the condition of synesthesia, people may experience such cross-modal correspondences to a perceptual degree (e.g., literally seeing sounds). So far, no study has addressed the question whether nonhuman animals share cross-modal correspondences as well. To establish the evolutionary origins of cross-modal mappings, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
174
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(190 citation statements)
references
References 55 publications
11
174
3
2
Order By: Relevance
“…Contrary to our expectations, though, the results of Experiment 1 revealed that the crossmodal correspondence between auditory pitch and visual brightness-the existence of which has been demonstrated by a number of researchers in adults, young children, and even chimpanzees (e.g., Hubbard, 1996;Ludwig et al, 2011;Marks, 1987;Martino & Marks, 1999;Melara, 1989;Mondloch & Maurer, 2004)-did not influence participants' performance on the pip-and-pop task, at least not when the congruency of the crossmodal correspondence (i.e., congruent vs. incongruent) was varied randomly on a trial-by-trial basis. The results of Experiment 1 therefore seem to corroborate the view that it is mainly the temporal information concerning the auditory signal, and not some other quality, such as its pitch, that is integrated with the visual signal.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Contrary to our expectations, though, the results of Experiment 1 revealed that the crossmodal correspondence between auditory pitch and visual brightness-the existence of which has been demonstrated by a number of researchers in adults, young children, and even chimpanzees (e.g., Hubbard, 1996;Ludwig et al, 2011;Marks, 1987;Martino & Marks, 1999;Melara, 1989;Mondloch & Maurer, 2004)-did not influence participants' performance on the pip-and-pop task, at least not when the congruency of the crossmodal correspondence (i.e., congruent vs. incongruent) was varied randomly on a trial-by-trial basis. The results of Experiment 1 therefore seem to corroborate the view that it is mainly the temporal information concerning the auditory signal, and not some other quality, such as its pitch, that is integrated with the visual signal.…”
Section: Discussioncontrasting
confidence: 55%
“…Further support for this notion comes from experiments, in which this crossmodal correspondence influenced the behavior of prelinguistic children (Mondloch & Maurer, 2004), and even of chimpanzees (Ludwig et al, 2011).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Now, this might be attributable to researchers having looked preferentially at those crossmodal influences that have been formed by associating various cues relative to the same object (e.g., following the unity assumption, considered as a crucial factor in multisensory research since Welch & Warren, 1986; see also Vatakis & Spence, 2007). However, effects that are not limited to these cases have been demonstrated in those broader crossmodal correspondences between sometimes distinctly presented objects whose dimensions happen to feel congruent: Higher-pitched sounds can facilitate the detection of brighter objects, even without coming from or being attributed to the same source or object (e.g., Klapetek, Ngo, & Spence, 2012;Ludwig, Adachi, & Matzuzawa, 2011). As we detail below, this draws attention to the need for further investigation in the case of associations holding between olfaction and musical features, and it indicates a few of the directions along which research could profitably be pursued (see Table 2 and below).…”
Section: Underevidenced Behavioral Effectsmentioning
confidence: 99%